Efektivitas Model Experiential Learning dalam Meningkatkan Kemampuan Berbicara Siswa Kelas X di MBI Amanatul Ummah - Rifki, Muhammad; Hafidz, Muhammad; Annisa, Maryam Nur (Prosiding Konferensi Nasional Bahasa Arab, 2023)
The purpose of this research to know (1) the application of the experiential learning model toimprove the speaking skill of student class X MBI Amanatul Ummah; (2) the effectiveness ofexperiential learning model for improving the speaking skill of student class X MBI AmanatulUmmah. This research uses quantitative approach with type of experiment. In this research, therewere two groups, the experimental group and control group. The research instrument consists ofobservation, interview and test (pre-test and post-test). The result of this research are: (1) theapplication of experiential learning model to improve the speaking skill of students class X MBIAmanatul Ummah namely with four concrete steps are in accordance with the theory at the coreof learning. The four steps are: (a) concrete experience; (b) reflective observation; (c) abstractconceptualitation; (d) active experimentation. In this research, reseacher used direct andgrammatical tarjamah methods. (2) this experiential learning model proved to be quite effectivein improving speaking skill of student class X at MBI Amanatul Ummah with an N-Gain value of56,5% which means that it has been categorized as quite effective.